Distribution characteristics, sources and ecological risk of antimony in the surface sediments of Changjiang Estuary and the adjacent sea, East China. (December 2018) - Zhuang, Wen; Lai, Xiaoying; Wang, Qian; Liu, Yongxia; Chen, Qing; Liu, Chang
Abstract: The distribution characteristics, sources and ecological risk of antimony (Sb) in the surface sediments of Changjiang Estuary and the adjacent sea were studied. Sb concentrations ranged from 0.320 to 0.968 μg g −1 with mean value of 0.577 μg g −1 . Sb concentrations were relatively high in sediments of the south Yellow Sea, the Hangzhou Bay mouth and the inner Changjiang Estuary. The variation trend of Sb concentrations was controlled by hydrodynamics, Al/Fe/Mn oxides. Sb also showed strong chalcophile property. Correlation analysis and enrichment factor showed Sb came mainly from natural sources. Total Sb sediment flux in the study area was 446.3 t/yr. The Changjiang River, the Yellow River and atmospheric inputs accounted for 85.7%, 13.9%, and 0.4% of the total sediment Sb flux, respectively. The result of potential ecological index indicated the very low Sb concentrations could hardly threat the ecological environment of the study area. Highlights: Big rivers are the main contributors to Sb in surface sediment of the study area. The distribution characteristics of Sb are mainly influenced by ocean currents. Sb is mainly from natural sources and causes no pollution to the study area.